2019
DOI: 10.3390/ma12213624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanosilica on Mechanical Properties and Microstructure of PVA Fiber-Reinforced Geopolymer Composite (PVA-FRGC)

Abstract: This paper presents the effects of various nanosilica (NS) contents on the mechanical properties of polyvinyl alcohol (PVA) fiber-reinforced geopolymer composites (PVA-FRGC). Microstructure analysis with X-ray diffraction (XRD) and scanning electron microscopy (SEM) was used to characterize the geopolymer composites. The results showed that the mechanical properties in terms of compressive strength, impact strength, and flexural behavior were improved due to the addition of NS to the PVA-FRGC. The optimum NS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 21 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The extraction of river sand causes a change in river bed level and hydrological strata, affecting the regular stream directions [ 1 , 2 , 3 ]. Furthermore, cement production requires substantial energy and emits a large amount of carbon dioxide [ 4 , 5 ]. It was reported that one ton of ordinary Portland cement (OPC) production can release around 0.85 ton of carbon dioxide, which ultimately causes around 5–8% of total emissions in the world [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of river sand causes a change in river bed level and hydrological strata, affecting the regular stream directions [ 1 , 2 , 3 ]. Furthermore, cement production requires substantial energy and emits a large amount of carbon dioxide [ 4 , 5 ]. It was reported that one ton of ordinary Portland cement (OPC) production can release around 0.85 ton of carbon dioxide, which ultimately causes around 5–8% of total emissions in the world [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mining of natural river sand causes changes in the direction of river flows and alters hydrological strata and river bed levels [20]. In addition to cement production, concrete casting requires substantial energy, consumes natural limestone, and is responsible for 5-7% of the world's total carbon dioxide emissions [21][22][23][24][25][26]. Therefore, research on the appropriate and sustainable substitutions of natural and conventional ingredients in concrete is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymers are a class of inorganic aluminosilicate-binding materials with an amorphous or semicrystalline three-dimensional structure [22]. The production of a geopolymer is associated with the reaction of aluminosilicate raw materials with alkaline activators, and therefore requires a substantial source of silica [24]. WG powder can be used as a precursor, fine aggregate, and activator in the production of cement-free geopolymer binders and geopolymer concretes [16,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of the effect of nanoparticles is not only crucial for the general improvement of geopolymer concrete but also has specific benefits for the development of fiber-reinforced geopolymer concrete. The combination of fibers and nanoparticles leads to reduced degradation of the fiber materials and results in better durability of the geopolymer composites [ 57 , 64 , 65 , 66 , 67 ]. Assaedi et al investigated the influence of the nano-silica content on the mechanical properties and durability of a geopolymer concrete reinforced with flax fibers [ 57 ].…”
Section: Natural Fibersmentioning
confidence: 99%